DIFFERENCES OF ATTACHMENT STYLES TO FATHERS BETWEEN EARLY ADOLESCENT MALE AND FEMALE - Fatmawati, Fatmawati (Ar Raniry : International Journal of Islamic Studies, 2017)
Many opinions state that girls have a tendency to be closer to their fathers than boys. This is because fathers usually reveal soft attitude and a kind way of talking toward his daughter. In addition, fathers also succumb to the demands of his daughter. Conversely, with his son, fathers are usually much more 'rough and tough'. So, girls feels more secure to their fathers than boys. The objective of this study was to determine the differences of attachment style to fathers between early adolescent male and female in seventh grade classes of Junior High School 19 Banda Aceh. The number of samples taken were 60 students. A rating scale was used for collecting data, namely Adult Attachment Scale (AAS). The result obtained from the T-Tests showed there was no significant differences of attachment style to fathers between early adolescents male and female in seventh grade classes of Junior High School 19 Banda Aceh. However, early adolescents prefer to have close attachment style with their fathers.